"Alternative history" as a factor of the genre transformation in the modern novel (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article gives a broad outline of the notion «the alternate story», the reasons of in creasing its influence in postmodern art and a variety of its functions in different types of fiction prose ranging from fantasy and myth to biographical and historical assumption.
Keywords: «alternate story»; «uchronia»; canonical myth; reconstruction of history; alternate biography